PENGARUH KOMPETENSI GURU DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP PRESTASI BELAJAR SISWA DI SMP SIRATUL ISLAM DESA PORDAPOR KECAMATAN GULUK-GULUK - Moh. Labib Anis; Endang Widyastuti (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2026)
Education is a form of long-term investment that plays a vital role in developing the quality of human resources and the sustainability of world civilization. The purpose of this study is to analyze the extent to which teacher competence and the principal's leadership style influence student achievement. In this study, teacher competence and principal leadership function as independent variables, while the dependent variable is student achievement. The subjects of this study were 54 students, all of whom came from Siratul Islam Junior High School. Data analysis was conducted using a multiple linear regression approach, which began with a validity test of the measurement instrument, then continued with testing classical assumptions such as normality, multicollinearity, heteroscedasticity, and linearity. For hypothesis testing, statistical tests were used individually (t-test) and together (F-test). The results of the analysis indicate that teacher competence significantly contributes positively to student achievement, indicated by a significance value of 0.000, which is far below the threshold of 0.05. In addition, principal leadership was also proven to have a significant positive influence on student learning outcomes, with a significance value of 0.038.